The Relationship of Stimulation By People To The Development Of Toddlers: Literature Review - Metty Nurherliyany; Yuyun Rahayu; Agiv Yogari (LPPM STIKes Muhammadiyah Ciamis, 2019)
Background: Development (development) is a change that is quantitative and qualitative. Development is the increase (skill) structure and function of the body that is more complex, in a regular and predictable pattern. Stimulation of development is very important in child development and is the forerunner of the learning process of children in the form of educating and training. Children who get targeted and regular stimulation will develop faster than children who are less stimulated. the act of providing stimulation to the child is to help the child achieve the optimal level of development or as expected. Objective: To determine the effect of elderly exercise on pain scale in patients with rheumatoid arthritis at the Ciamis Public Health Center Method: The method used in this literature review is a search sourced from an electronic data base including DOAJ and Google Scholar from 2015-2020 using 15 journals related to parent stimulation, toddler development, the relationship of parent stimula to the development of a toddler. The results of the literature review indicate that there is a relationship between parent stimula on the development of a toddler. Result: The results of the literature review indicate that there is a relationship between parent stimula on the development of a toddler. Based on 15 analyzed journals obtained by researchers, stated that growth stimulation is a factor influencing toddler development. The interaction between the environment and stimuli can help the brain develop neurological structures. Conclusion: Based on studies from all journals, it states that there is a relationship of stimulation provided by parents to toddlers on their development